Persepsi Guru TK dan SD Terhadap Pelaksanaan Transisi PAUD ke SD yang Menyenagkan di Kota Gorontalo - Mutmainna Ts Bullah; Wenny Hulukati; Muhamad Zubaidi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to understand teachers' perceptions of the implementation of a joyful transition from Early Childhood Education to elementary school, as well as to identify the obstacles in carrying out this transition. The research method employed descriptive quantitative. Data collection was conducted through questionnaires distributed to 20 respondents and interviews with 5 participants. The results showed the perception of kindergarten teachers in schools such as TK Pembina Kec. Kota Utara Kindergarten, TK Alkhairat Kindergarten, TK Al-Huda Kindergarten, TK Aisyiyah Bustanul Athfal VII Kindergarten, and TK Aster Kindergarten were categorized as